Comparison of Tracheal Wash and Bronchoalveolar Lavage Cytology in 154 Horses With and Without Respiratory Signs in a Referral Hospital Over 2009−2015 - Rossi, Heini; Virtala, Anna-Maija; Raekallio, Marja; Rahkonen, Emmi; Rajamäki, Minna M.; Mykkänen, Anna (Frontiers in Veterinary Science, 2018)
Most equine lower respiratory diseases present as increased airway neutrophilia, which can be detected in tracheal wash (TW) or bronchoalveolar lavage fluid (BALF) cytology samples. The aim was to compare the TW and BALF results in a population of client-owned horses with and without clinical respiratory disease signs. A secondary aim was to determine the sensitivity (Se) and specificity (Sp) of TW and BALF neutrophilia in detecting respiratory disease. The cut-off values for neutrophils were also evaluated. Retrospective data from 154 horses of various breeds that had been subject to both TW and BAL sampling at rest during 2009−2015 was used. The horses were divided into 3 groups based on the presenting signs, physical examination and endoscopy mucus score. A neutrophil count of >20% in TW and >5% in BAL were considered abnormal. Cytology results between groups, correlations between TW and BALF cell types, and tracheal mucus score were analyzed. Two graph receiving operating characteristic (ROC) curves of the neutrophil percentage values of TW and BALF were created to determine the optimal cut-off values and to calculate the diagnostic Se and Sp for diagnosing airway inflammation in horses with and without clinical respiratory signs. The Se and Sp of TW and BALF neutrophil percentages were further estimated using a 2-test 1-population Bayesian latent class model. The two tests showed substantial agreement and only 17.5% of the horses were classified differently (healthy vs. diseased). The neutrophil percentage was found to correlate between TW and BALF. The sensitivity and specificity of TW was generally higher than for BAL when estimated with area under the curve or Bayesian model. Cut-off values of 17.7% for TW and 7% for BALF were indicated by the ROCs. We conclude that TW is a more sensitive and specific method in our patient population. We suggest that the current neutrophil cut-off values of 20% for TW and 5% for BALF would still be appropriate to use in clinical diagnosis of airway inflammation. However, further studies with other cell types and in other populations are warranted to determine the best sampling method for individual horses.